2014
DOI: 10.3748/wjg.v20.i46.17491
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for postoperative pancreatic fistula following pancreaticoduodenectomy

Abstract: A pancreatic duct diameter ≤ 3 mm is an independent risk factor for POPF. External stent drainage of pancreatic secretion may reduce CR-POPF mortality and POPF severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 40 publications
3
50
1
5
Order By: Relevance
“…The incidence of all POPF can vary greatly, from 4% in specific subgroups to more than 30%, according to the indication for pancreatoduodenectomy: POPF rate used to be lower in cases of chronic pancreatitis or ductal adenocarcinoma, compared with ampulloma and endocrine tumours . In our series, POPF occurred in 25% of patients, and particularly in cases of endocrine tumours (23.9 versus 6.4% of endocrine tumours without POPF, P < 0.01), which is in accordance with the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The incidence of all POPF can vary greatly, from 4% in specific subgroups to more than 30%, according to the indication for pancreatoduodenectomy: POPF rate used to be lower in cases of chronic pancreatitis or ductal adenocarcinoma, compared with ampulloma and endocrine tumours . In our series, POPF occurred in 25% of patients, and particularly in cases of endocrine tumours (23.9 versus 6.4% of endocrine tumours without POPF, P < 0.01), which is in accordance with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…The size of the main pancreatic duct, assessed either preoperatively on imaging or intraoperatively by the surgeon, has been identified as predictive factor of POPF, by many authors . The most widely used cut‐off value for the occurrence of POPF was 3 mm . Location of pancreatic duct in the stump has been also studied, with conflicting results: Yamamoto et al .…”
Section: Discussionmentioning
confidence: 99%
“…Systemic factors, such as elderly age (>65 years), epigastrium surgery, preoperative nutritional status, preoperative jaundice, preoperative hemoglobin, hypertension, diabetes and other associated underlying diseases. However, Liu Qiuyu et al found that age, gender, body mass index, hypertension, diabetes mellitus, history of jaundice, serum albumin level, and blood loss volume have no statistical difference related to the morbidity of POPF after multivariate analysis [4] . 2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that risk factors for POPF included a higher BMI, soft pancreatic texture and a smaller pancreatic duct size . Several fistula risk scoring systems have been published , with one tested for its ability to predict POPF in a multicenter cohort .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even after controlling for confounding factors and bias, which are limitations of nonrandomized retrospective studies, PGA mesh could prevent clinically relevant POPF and its complications. Studies have reported that risk factors for POPF included a higher BMI, soft pancreatic texture and a smaller pancreatic duct size [31][32][33][34]. Several fistula risk scoring systems have been published [17,35], with one tested for its ability to predict POPF in a multicenter cohort [36].…”
Section: Discussionmentioning
confidence: 99%